Control of spatial deposition of electrospun fibre using electric field manipulation - Nurfaizey , Abdul Hamid; Stanger, Jonathan; Tucker, Nick; Buunk, Neil; Wood, Alan R.; Staiger, Mark (SAGE Publications Inc., 2014)
A significant challenge in the synthesis of uniform membranes via electrospinning is achieving a spatially uniform deposition of electrospun fibres. The problem is more pronounced in the case of a multi-spinneret system due to self repulsion between the jets. In this study, electric field manipulation (via auxiliary electrodes) is explored as a potential technique for controlling the spatial deposition area of electrospun fibre. It was observed experimentally that the location and size of the deposition area can be moved linearly in response to the applied voltages at the auxiliary electrodes. Finite element analysis (FEA) was used to simulate the electric field strength and distribution at a given applied voltage and its effect on the flight path of electrospun fibre. Comparisons between experiments and simulations were made in evaluating the accuracy of simulations. The adaptation of this technique in production would provide a method of controlled deposition for producing uniform electrospun fibre membranes.